The estimation of live weight from body measurements in Yankasa sheep - Afolayan, R.A.; Adeyinka, Isaac A.; Lakpini, C.A.M. (2006)
Live body weight measurements of weight, height, length, girth, stifle- and hip-width and measure of muscularity (ratio of stifle to hip width) were monitored on 258 yankasa sheep stratified into age categories of 1 to over 3 years determined mostly from records and partly by dentition. These animals are from purebred Yankasa sheep kept as a part of the open nucleus-breeding scheme of the National Animal Production Research Institute, Shika, Zaria, Nigeria. The effect of sex, type of birth and age group of lambs on live measurements and muscularity were analyzed by least-squares procedures. All variables examined, except sex, had significant (P